GREEN HOSPITAL IMPLEMENTATION IN INDONESIA: A LITERATURE REVIEW - Octavianus Marshal; Nico Christian Sunaryo; Sylvia Jessy Kurniawan; Deltania Herwendanasari; Engelbert Hariyanto; Sri Andarini (Journal of Community Health and Preventive Medicine, 2021)
Hospital is one of the institutions that use a considerable amount of energy and contribute the largest amount of waste. In order to reduce its impact, initiatives have emerged in the form of green hospitals for the effective use of resources. Although there are standard criteria for each country in applying environmentally friendly buildings in each country, there is still no internationally referenced certification. This study intends to compare the implementation of green hospitals in various hospitals in Indonesia. The comparisons will be taken from the elements of a green hospital, namely energy efficiency, green building design, alternative energy generation, transportation, food, water, and the availability of green open space. This research type is a literature review, with data taken from an online database. The online databases used are Science Direct and Google Scholar. The criteria used are elements of the implementation of green hospitals in Indonesia, and must mention the name of the hospital or the area where the research was carried out. There were 12 studies that matched the inclusion criteria. It can be seen that there are various efforts by hospitals in Indonesia in implementing green hospitals. However, there is unpreparedness in the application of all of its elements, especially in the transportation and food elements.